Hydrogen bond donors and acceptors are generally depolarized in α‐helices as revealed by a molecular tailoring approach. Issue 23 (17th May 2019) - Kondo, Hiroko X.; Kusaka, Ayumi; Kitakawa, Colin K.; Onari, Jinta; Yamanaka, Shusuke; Nakamura, Haruki; Takano, Yu
Abstract : Hydrogen‐bond (H‐bond) interaction energies in α‐helices of short alanine peptides were systematically examined by precise density functional theory calculations, followed by a molecular tailoring approach. The contribution of each H‐bond interaction in α‐helices was estimated in detail from the entire conformation energies, and the results were compared with those in the minimal H‐bond models, in which only H‐bond donors and acceptors exist with the capping methyl groups. The former interaction energies were always significantly weaker than the latter energies, when the same geometries of the H‐bond donors and acceptors were applied. The chemical origin of this phenomenon was investigated by analyzing the differences among the electronic structures of the local peptide backbones of the α‐helices and those of the minimal H‐bond models. Consequently, we found that the reduced H‐bond energy originated from the depolarizations of both the H‐bond donor and acceptor groups, due to the repulsive interactions with the neighboring polar peptide groups in the α‐helix backbone. The classical force fields provide similar H‐bond energies to those in the minimal H‐bond models, which ignore the current depolarization effect, and thus they overestimate the actual H‐bond energies in α‐helices. © 2019 The Authors. Journal of Computational Chemistry published by Wiley Periodicals, Inc. Abstract : Hydrogen‐bond (H‐bond) energies in α‐helices were systematically examined by DFT calculations with a molecular tailoring approach. H‐bond energies in α‐helices were always weaker than the minimal H‐bond models, in which only H‐bond donor and acceptor exist with the capping methyl groups. The reduced H‐bond energy originated from the depolarizations of both the H‐bond donor and acceptor groups, due to the repulsive interactions with the neighboring polar peptide groups in the α‐helix backbone.